2021
DOI: 10.2147/cmar.s295675
|View full text |Cite
|
Sign up to set email alerts
|

Low-Coverage Sequencing of Urine Sediment DNA for Detection of Copy Number Aberrations in Bladder Cancer

Abstract: Purpose Chromosomal copy number aberrations (CNAs) are a hallmark of bladder cancer and a useful target for diagnostic explorations. Here we constructed a low-coverage whole-genome sequencing method for the detection of CNAs in urine sediment DNA from patients with bladder cancer. Patients and Methods We conducted a prospective study using urine sediment samples from 65 patients with bladder tumors, including 54 patients with bladder cancer and 11 patients with benign b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…Based on our data, lncRNA CDKN2B-AS1 played an oncogenic factor in breast cancer. It is consistent with the previous other studies about its role in most cancers, which indicated that CDKN2B-AS1 exerted a pro-cancer effect [40][41][42]. For examples, in renal clear cell carcinoma, lncRNA CDKN2B-AS1 affected the malignancy through epigenetically activating NUF2 (NUF2 Component of NDC80 Kinetochore Complex) transcription [16].…”
Section: Discussionsupporting
confidence: 91%
“…Based on our data, lncRNA CDKN2B-AS1 played an oncogenic factor in breast cancer. It is consistent with the previous other studies about its role in most cancers, which indicated that CDKN2B-AS1 exerted a pro-cancer effect [40][41][42]. For examples, in renal clear cell carcinoma, lncRNA CDKN2B-AS1 affected the malignancy through epigenetically activating NUF2 (NUF2 Component of NDC80 Kinetochore Complex) transcription [16].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, COX6c has been proposed as a potential participant in the chromosomal organization in a retroperitoneal lipoma instance [ 69 ]. Yun et al also found that COX6c is a key gene in bladder cancer tumors by detecting bladder cancer chromosomal copy number aberrations in urinary sediment [ 70 ].…”
Section: Cox6c and Diseasesmentioning
confidence: 99%
“…The most recent study found a sensitivity of 11% for analysis in plasma 67 , which was supported by the majority of other studies describing sensitivities of less than 20% 67,[85][86][87][88] . Two studies reported specificities (96% and 100%) 67,89 , and two studies reported concordance rates (41% and 42%) 86,88 .…”
Section: Hltfmentioning
confidence: 62%
“…All six studies on helicase-like transcription factor (HLTF) hypermethylation analysis for the purpose of CRC detection used qMSP and described large cohorts of more than 100 patients 67,[85][86][87][88][89] .…”
Section: Hltfmentioning
confidence: 99%
See 1 more Smart Citation